Aqueous Extract and Polysaccharide of Aconiti Lateralis Radix Induce Apoptosis and G0/G1 Phase Cell Cycle Arrest by PI3K/AKT/mTOR Signaling Pathway in Mesangial Cells. (22nd April 2022) - Li, Xingyao; An, Peng; Zhao, Yanhong; Cai, Zimo; Ye, Bingyu; Wang, Yafeng; Wang, Wenfang; Gao, Qi; Li, Liuyun; Zhang, Tao; Wu, Xili
Abstract : Mesangial proliferative glomerulonephritis (MesPGN) is a common renal disease that lacks effective drug intervention. Aconiti Lateralis Radix (Fuzi), a natural Chinese medical herb, is found with significant therapeutic effects on various diseases in the clinic. However, its effects on MesPGN have not been reported. This study is aimed to discuss the therapeutic effects of the aqueous extract of Aconiti Lateralis Radix (ALR) and the polysaccharides of Aconiti Lateralis Radix (PALR) on MesPGN as well as the underlying mechanism. In this study, we, firstly, studied the anti-MesPGN mechanism of ALR and PALR. ALR and PALR inhibit the proliferation of the mesangial cells through the PI3K/AKT/mTOR pathway, induce the G0/G1 phase of block and apoptosis, inhibit the activity of Cyclin E and CDK2, increase the expression of Bax, cleaved caspase-8/caspase-8, and cleaved caspase-3/caspase-3 proteins, and effectively inhibit the growth of the mesangial cells. Overall, our data suggest that ALR and PALR may be potential candidates for MesPGN and that PALR is more effective than ALR.